2015
DOI: 10.1016/j.jrras.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heavy metal content in Qaroun Lake, El-Fayoum, Egypt. Part I: Bottom sediments

Abstract: Available online xxx Keywords:Qaroun Lake sediments Grain size Heavy metals Igeo Cf and Cd contamination indices a b s t r a c t This paper was undertaken in order to assess the extent of contamination in bottom sediments of Qaroun Lake, El-Fayoum, Egypt. Sediment samples were analyzed for grain size distribution and heavy metals concentration. Ten heavy metals were determined (in ppm) by X-Ray Fluorescence Spectrometry. The average concentration values in sediments are 2.99 (As), 124.89 (Cr), 38.91(Cu), 14.21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 25 publications
(26 reference statements)
2
22
0
1
Order By: Relevance
“…Table 5. Classes of pollution indices (adopted from El-Amier et al, 2017;El-Sayed et al, 2015;Zahra et al, 2014) and contamination categories of heavy metal in Lake Naivasha sediment based on Contamination Factor (CF), Enrichment Factor (EF) and Geoaccumulation Index (I geo given by Lake Naivasha Riparian Association (LNRA) during the survey period is also highly appreciated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 5. Classes of pollution indices (adopted from El-Amier et al, 2017;El-Sayed et al, 2015;Zahra et al, 2014) and contamination categories of heavy metal in Lake Naivasha sediment based on Contamination Factor (CF), Enrichment Factor (EF) and Geoaccumulation Index (I geo given by Lake Naivasha Riparian Association (LNRA) during the survey period is also highly appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…where, C metal is the total metal concentration and C background represents the average background value of the metal in sediment. The CF was then classified into four grades as given by Al-Mur et al (2017); El-Sayed et al (2015) and Sabo, Gani, and Ibrahim (2013). Another index that was used in determining the contamination level was I geo .…”
Section: Pollution Assessment Of Heavy Metal In Sedimentmentioning
confidence: 99%
See 2 more Smart Citations
“…Moore et al (2009) reported that that geoaccumulation index values were 4.5 for Pb in and 2.8 for Se in the Maharlu Aaline Lake, Iran. Geoaccumulation index values calculated 8.68 in East, 0.88 in central and 1.36 in West of Qaroun Lake sediments, Egypt, by El-Sayeda et al (2015). Also, the geoaccumulation index values for Pb were 2.02 in the southwest of Nigeria (Asibor et al 2015), and 3.42 for in the Gulf of Thailand (Jakkapan et al 2015).…”
Section: Resultsmentioning
confidence: 99%